Utility and pitfalls of the electrocardiogram in the evaluation of cardiac amyloidosis. Issue 4 (14th May 2022) - Ng, Perryn Lin Fei; Lim, Yoke Ching; Evangelista, Lauren Kay Mance; Wong, Raymond Ching Chiew; Chai, Ping; Sia, Ching Hui; Loi, Hoi Yin; Yeo, Tiong Cheng; Lin, Weiqin
Abstract: Background: Cardiac amyloidosis is a protein misfolding disorder involving deposition of amyloid fibril proteins in the heart. The associated fibrosis of the conduction tissue results in conduction abnormalities and arrhythmias. "Classical" electrocardiogram (ECG) findings in cardiac amyloidosis include that of low voltage complexes with increased left ventricular wall thickness on echocardiography. However, this "classical" finding is neither sensitive nor specific. As cardiac amyloidosis is associated with a generally poor prognosis, the need for early recognition of this disease is important given the availability of new treatment options. In this review, we highlight 3 cases of patients with cardiac amyloidosis. Although presenting with typical clinical signs and symptoms, ECG for all 3 patients was not consistent with the classical findings described. They underwent further diagnostic tests which clinched the diagnosis of cardiac amyloidosis, allowing patients to receive targeted treatment. Through the review of the literature, we will highlight the different ECG patterns in patients with different types of cardiac amyloidosis and clinical scenarios, as well as the pitfalls of using ECG to identify the condition. Lastly, we also emphasize the current paradigms in diagnosing cardiac amyloidosis through the non‐invasive methods of echocardiography, cardiac magnetic resonance imaging, and nuclear technetium‐pyrophosphate imaging. Conclusions: Electrocardiogram is often the first investigation used in evaluating many cardiac disorders, including cardiac amyloidosis. However, classical features of cardiac amyloidosis on ECG are often not present. A keen understanding on the ECG features of cardiac amyloidosis and knowledge of the diagnostic workflow is important to diagnose this condition. Abstract : Electrocardiogram (ECG) of a patient with transthyretin amyloid cardiomyopathy, without the classical ECG findings of cardiac amyloidosis. This demonstrates the heterogeneity of ECG findings in cardiac amyloidosis. A high degree of suspicion is often necessary, to further evaluate for possible cardiac amyloidosis.